2020
DOI: 10.1186/s13643-020-01363-0
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive oxygenation strategies in adult patients with acute respiratory failure: a protocol for a systematic review and network meta-analysis

Abstract: Background: Acute hypoxemic respiratory failure is one of the leading causes of intensive care unit admission and is associated with high mortality. Noninvasive oxygenation strategies such as high-flow nasal cannula, standard oxygen therapy, and noninvasive ventilation (delivered by either face mask or helmet interface) are widely available interventions applied in these patients. It remains unclear which of these interventions are more effective in decreasing rates of invasive mechanical ventilation and morta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This review has been conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta-analysis Protocols statement extension for network meta-analysis . The protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO; CRD42019121755) and has been published . No institutional review board approval was required because all study data had been published previously and this study did not include individual patient data.…”
Section: Methodsmentioning
confidence: 99%
“…This review has been conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta-analysis Protocols statement extension for network meta-analysis . The protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO; CRD42019121755) and has been published . No institutional review board approval was required because all study data had been published previously and this study did not include individual patient data.…”
Section: Methodsmentioning
confidence: 99%
“…In South Korea, the first confirmed case of COVID-19 was reported on January 20, 2020. [ 1 ] In the city of Daegu, the fourth largest city of South Korea with 2.5 million residents, the first COVID-19 case was confirmed on February 18, 2020. Within days, the number of cases surged due to the community transmission within a secretive religious organization.…”
Section: Introductionmentioning
confidence: 99%
“…Results of the NIHR funded RECOVERY-RS trial were presented by Gavin D. Perkins (Birmingham, UK), who highlighted the need for international consensus on the use of noninvasive oxygen therapy in COVID-19 [ 43 , 44 ]. The RECOVERY-RS trial showed that while HFNO did not perform better than conventional oxygen therapy, CPAP decreased the need for mechanical ventilation at 30 days and reduced intensive care admission compared with conventional oxygen therapy [ 40 ].…”
Section: How Science Conquered Covid-19: From Big Platform Trials To ...mentioning
confidence: 99%